Study of Biological Factors Likely to Influence Sensitivity to Dry Notch* Disease of Rubber Tree in Three Rubber Production Zones of Cote D’ivoire - Dominique, Zoh Olivia; Tonessia, Dolou Charlotte; Soumahin, Éric Francis; Joseph, Kouamé Kouassi James; Doumbia, Amadou (International Journal of Environment, Agriculture and Biotechnology, 2023)
Rubber production in rubber trees is affected by dry notch disease, the cause of which has unfortunately not yet been fully elucidated. This study aims to evaluate the impact of biological factors on susceptibility to disease across agro-industrial companies in the West (Zagné), South-West (San-Pédro) and South-East (Anguédédou) zones of the Côte d’Ivoire. The method used is the recording of panel sick length (PSL) of rubber trees in relation to their clonal metabolisms and the attacks of the main pests of rubber trees such as Corynespora sp, Fomes sp and Loranthaceae. The results showed that the three cultivated clonal metabolic class were all affected by dry notch of rubber but at different levels with an average of 34.65 ± 1.77 %. Regarding pests, the study revealed that they significantly influence (Pr ˂ 0.05) the sensitivity to dry notch. Rubber trees attacked by Fomes sp displayed a higher rate of diseased notch (50.56 ± 20.30 %) than that of non-attacked rubber trees (30.58 ± 20 %). Similarly, rubber trees parasitized by Loranthaceae displayed higher PSL (38.41 ± 20.55 %) than those of rubber trees free (30.16 % ± 21.62 %). Only rubber trees attacked by Corynespora sp presented lower PSL (15.61 ± 13.69 %) than those of non-attacked rubber trees (39.76 ± 20.22 %). Depending on the different production zones, Loranthaceae infested rubber plantations more than the other two pests.